Spatial–Temporal pattern and evolutionary trend of eco-efficiency of real estate development in the yangtze river economic belt - Fan, Zhenggen; Deng, Zhikang; Qi, Yawei; Pan, JiaSen (Frontiers in Environmental Science, 2022)
The eco-efficiency of real estate development (RED) is an important indicator in evaluating the effectiveness of eco-civilization construction. Thus, analyzing its temporal evolution and spatial spillover effect can help to judge the degree of coordinated development between RED and eco-civilization construction in the Yangtze River Economic Belt (YREB). From an ecology-based angle of RED, the data of 108 cities in YREB from 2006 to 2020 were selected. Then, the Super-SBM model, Moran’s I model, and Markov chain model were used to measure the eco-efficiency value of RED and analyze its spatial–temporal evolutionary characteristics. Research results indicate that the eco-efficiency of RED in YREB increased by 7.3%. Differences were apparent in the regional eco-efficiency of RED, but the gap gradually narrowed, and the range decreased from 0.60 to 0.05. A positive spatial autocorrelation was observed in the eco-efficiency of RED, and the high–high (H-H) cluster areas showed a trend of expansion and transfer. The proportion of H-H cluster cities increased from 11% to 20%, whereas the low–low cluster areas showed a trend of small-scale diffusion. The eco-efficiency of RED exhibited consistently stable and “club convergence” characteristics. When the spatial spillover effect is ignored, the eco-efficiency of RED presents at least 55.1% probability to be maintained in the original state. By contrast, when the spatial spillover effect is considered, the probability can be increased, and the assimilation effect of transferring the eco-efficiency of RED can be enhanced. In the future, the overall eco-efficiency of RED in YREB can be improved by exploring new development technologies, establishing collaborative development mechanisms among cities, and adopting eco-protection-oriented reward and punishment policies.